Blood–retinal barrier breakdown in experimental coronavirus retinopathy: association with viral antigen, inflammation, and VEGF in sensitive and resistant strains - Vinores, Stanley A (J Neuroimmunol, 2001)
Intraocular coronavirus inoculation results in a biphasic retinal disease in susceptible mice (BALB/c) characterized by an acute inflammatory response, followed by retinal degeneration associated with autoimmune reactivity. Resistant mice (CD-1), when similarly inoculated, only develop the early phase of the disease. Blood–retinal barrier (BRB) breakdown occurs in the early phase in both strains, coincident with the onset of inflammation. As the inflammation subsides, the extent of retinal vascular leakage is decreased, indicating that BRB breakdown in experimental coronavirus retinopathy (ECOR) is primarily due to inflammation rather than to retinal cell destruction. Vascular endothelial growth factor (VEGF) is upregulated only in susceptible mice during the secondary (retinal degeneration) phase.